Biomechanical Characteristics of 3 Pivot-Shift Maneuvers for the Anterior Cruciate Ligament–Deficient Knee: In Vivo Evaluation With an Electromagnetic Sensor System. (November 2013) - Kitamura, Nobuto; Yokota, Masashi; Kondo, Eiji; Miyatake, Shin; Nagamune, Kouki; Yasuda, Kazunori
Background: A disadvantage of pivot-shift maneuvers is that the examiner has to subjectively evaluate the degree of pivot shift observed. It is unknown whether the various maneuvers are biomechanically identical. Purpose: To compare biomechanical features of 3 clinical maneuvers for the anterior cruciate ligament (ACL)–deficient knee: the pivot-shift test, the jerk test, and the N-test. Study Design: Controlled laboratory study. Methods: A total of 28 patients with an isolated ACL injury were examined by use of 3 pivot-shift maneuvers (pivot-shift test, jerk test, and N-test). An electromagnetic sensor system was used to evaluate the 3-dimensional knee kinematics of each patient's injured and uninjured knees during each maneuver. Peak coupled anterior tibial translation (pCAT) and maximal acceleration of posterior translation (APT) were measured relative to results during a flexion-extension motion in each test. Results: The pCAT of the pivot-shift test was significantly greater than that of both the jerk test and the N-test ( P = .0020 and P < .0001, respectively); there was no statistical difference in pCAT between the jerk test and the N-test. The APT of the N-test was significantly greater than that of both the pivot-shift test and the jerk test ( P < .0001), while there was no statistical difference between the pivot-shift and the jerk tests. There was no correlation between pCAT and APT in each test. Conclusion: The pivot-shift test, jerk test, and N-test have different biomechanical characteristics to induce the pivot-shift phenomenon in the ACL-deficient knee. The pivot-shift test produced the largest side-to-side difference in pCAT, whereas the N-test provoked the largest side-to-side difference in APT. Clinical Relevance: The biomechanical differences in pivot-shift maneuvers are caused by technical differences, and clinicians should understand these biomechanical differences while practicing the maneuvers. The electromagnetic sensor system is clinically useful for quantifying the pivot-shift phenomenon.